Functional Cytology of the Hepatopancreas of Palaemonetes argentinus (Crustacea, Decapoda, Caridea) Under Osmotic Stress - Díaz, Ana Cristina (2010)
The present work describes the effect of different salinities on the functional morphology of the P. argentinus hepatopancreas and analyses the tissue recovery after re-acclimation to freshwater. Adult prawns of both sexes at sexual rest were collected from a tributary of the Mar Chiquita coastal lagoon. The prawns were acclimated in aquaria to four salinity conditions: 0 (control), 8, 16 and 24‰. To evaluate the possible tissular recovery, after 60 days individuals from all the treatments were gradually acclimated to freshwater and maintained for other 30 days. Hepatopancreas samples were processed at the beginning of the trial and every 30 days using standard histological techniques for OM and TEM. The individuals from all the treatments, except the controls, showed a continuous weight decrease, and survival was lower when higher the salinity. At 30 days from the beginning of the experiment, hepatopancreas from 16 and 24‰ salinities showed an enlarged tubular lumen and an infolded basal lamina. Ultratructurally, nuclear retraction, cytoplasmolysis, and RER membranes separated with electron-dense content were observed in all the treatments except 0‰. After 60 days, profound alterations were observed with the three treatments. After the re-acclimation period, there was no reestablishment of the functional cytology. The tolerance to short-term salinity changes explains the capability of this prawn to inhabit in estuarine environments.